Workplace productivity and management practices - Polachek, S. W.; Tatsiramos, Konstantinos; Russo, Giovanni (Economist); Houten, Gijs van (Bingley, U.K. : Emerald Publishing Limited, 2021)
How firms are structured, the management practices they develop, as well as the way in which workers and managers interact can have wider implications for both the performance of the firm and the well-being of its workers. This volume contains ten original and innovative articles that investigate aspects related to workplace practices and productivity. Topics include the role of employee voice in the workplace, the link between unions, innovation and firms' investment, the relationship between job autonomy and hierarchy, the impact of personnel policies on firm performance, the consequences of incentives through discrete bonus compensation schemes for learning on the job, the repercussions of firm downsizing on worker's performance, the individual returns to entrepreneurship, the impact of private tutoring on college attendance, and the measurement of labor market transitions.
Chapter 1. What Do Workers Want? The Representation Gap at The Eu Establishment as Perceived by Their Workplace Representatives / John T. Addison and Paulino Teixeira -- Chapter 2. Union Effects on Product and Technological Innovation / Alex Bryson and Harald Dale-Olsen -- Chapter 3. A Simple Model of Hold-Up, Union Voice and Firm Investments / Fabio Berton, Stefano Dughera, and Andrea Ricci -- Chapter 4. Complex Job Designs and Layers of Hierarchy / Giovanni Russo and Gijs van Houten -- Chapter 5. Internal Labor Market Dimensions and Labour Productivity / Pedro S. Martins -- Chapter 6. Incentivizing Learning-By-Doing: The Role of Compensation Schemes / Joshua Graff Zivin, Lisa B. Kahn, and Matthew Neidell -- Chapter 7. Downsizing Announcements, Job Security Perceptions, and Worksite Performance / Guido Friebel, Matthias Heinz, Ingo Weller, and Nick Zubanov -- Chapter 8. The Returns to Enterpreneurship: Evidence from Matched Person-Firm Data / Mirjam van Praag and Arvid Raknerud -- Chapter 9. The Impact of Private Tutoring on Higher Education Outcomes: Evidence from South Korea / Tiloka de Silva -- Chapter 10. Job Finding and Separation Rates in an Economy with High Labor Informality / Nikita Céspedes Reynaga and N.R. Ramírez-Rondán.
Print version record.
Keywords: elektronické knihy; electronic books; Labor productivity; Industrial management; Business & Economics -- Management; Management & management techniques